2019
DOI: 10.1007/s40430-019-1656-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface integrity and machining performance during main/rough cut and trim/finish cut mode of WEDM on Ti–6Al–4V: effects of wire material

Abstract: Due to increased demand of dimensional accuracy and high precision of manufactured parts, wire electrical discharge machining (WEDM) became very popular, especially for 'difficult-to-cut' materials like titanium alloys. Grade 5 Ti alloy (Ti-6Al-4V) has enormous application in aerospace and biomedical fields. WEDM performance of Ti-6Al-4V is somewhat restricted due to its poor thermal conductivity, formation of hard and brittle carbide-/oxide-rich layer and often surface cracking which affect fatigue performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
2
15
0
1
Order By: Relevance
“…Considering brevity, the SEM images are only presented for the low and high values of those parameters (TON, TOFF, VGAP) which showed a high influence on the surface roughness parameters. From Figure 10a-e, the surface morphology of the microchannels reveals characteristics such as microcraters, microvoids, microglobules, resolidified material, microcracks and microholes, and similar defects were also reported in the previous studies [25,32,33]. The distribution of the microcracks on the WEDM machined surface was small.…”
Section: Surface Morphologysupporting
confidence: 79%
See 2 more Smart Citations
“…Considering brevity, the SEM images are only presented for the low and high values of those parameters (TON, TOFF, VGAP) which showed a high influence on the surface roughness parameters. From Figure 10a-e, the surface morphology of the microchannels reveals characteristics such as microcraters, microvoids, microglobules, resolidified material, microcracks and microholes, and similar defects were also reported in the previous studies [25,32,33]. The distribution of the microcracks on the WEDM machined surface was small.…”
Section: Surface Morphologysupporting
confidence: 79%
“…For measuring the recast layer thickness, SEM images of the cross-sectioned samples were taken. The average recast layer thickness was calculated as the recast layer area measured from the SEM micrograph divided by the micrograph length, as illustrated in [25]. The area of the recast layer was determined through manual inspection, and later using the ImageJ software (National Institutes of Health, Bethesda, ML, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the presence of irregular or uneven shapes of debris, melted material deposition, craters, micro-cracks, spherical droplets (SD) and pockmarks on the WEDMed surface. The previous authors also reported similar studies Kumar et al (2014), Jadam et al (2019). The irregular or uneven shapes of debris are formed due to the unflushed molten materials by dielectric flushing, and it re-solidified on the surface.…”
Section: Resultssupporting
confidence: 60%
“…14 The fourth strategy is magnetic effects between the tool and the workpart, 3 and the final strategy is the trim cutting method to decrease the dimensional deviation using WEDM. 6,15 Aforesaid discussed important strategies are the most favorable way to improve corner accuracy. It is observed that most WEDM manufacturers suggest that the modification of process parameters can improve the corner accuracy, 5 and also this statement supported by the above literature.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%